A proximal interphalangeal joint custom-made orthosis in trigger finger: Functional outcome. (September 2021) - Pataradool, Kawee; Lertmahandpueti, Chayanin
Introduction: Trigger finger is a common and functionally limiting disorder. Finger immobilization using an orthotic device is one of the conservative treatment options for treating this condition. The most common orthosis previously described for trigger finger is metacarpophalangeal joint immobilization. There are limited studies describing the effectiveness of proximal interphalangeal joint orthosis for treatment of trigger finger. Methods: This study was a single group pretest-posttest design. Adult patients with single digit idiopathic trigger finger were recruited and asked to wear a full-time orthoses for 6 weeks. The pre- and post-outcome measures included Quick-DASH score, the Stages of Stenosing Tenosynovitis (SST), the Visual Analogue Scale (VAS) for pain, the number of triggering events in ten active fists, and participant satisfaction with symptom improvement. Orthotic devices were made with thermoplastic material fabricated with adjustable Velcro tape at the dorsal side. All participants were given written handouts on this disease, orthotic care and gliding exercises. Paired t-tests were used to determine changes in outcome measures before and after wearing the orthosis. Results: There were 30 participants included in this study. Evaluation after the use of PIP joint orthosis at 6 weeks revealed that there were statistically significant improvements in Quick-DASH score from enrolment (mean difference −29.0 (95%CI −34.5 to −23.4); p < 0.001), SST (mean difference −1.4 (95%CI −1.8 to −1.0); p < 0.001) and VAS (mean difference −3.4 (95%CI −4.3 to −2.5); p < 0.001). There were no serious adverse events and patient satisfaction with the treatment was high. Conclusions: Despite our small study size, the use of proximal interphalangeal joint orthosis for 6 weeks resulted in statistically significant improvements in function, pain and triggering, and also high rates of acceptance in patients with isolated idiopathic trigger finger.